A formação continuada dos gestores educacionais - Inforsato, Edson do Carmo [UNESP]; Santana, Andreia da Cunha Malheiros (My University, 2011)
In this article the issue of continuing education is associated with the needs analysis, according to the theoretical used. The aim of this study is identify the factors that motivate or discourage the continuing education of educational managers (principals, vice-principals, coordinators and educational assistants) into ten public schools in the city of Araraquara. The managers have been heard through questionnaire, report narratives and interviews. The position of the Education Department have been got through an interview. According to these managers reports it was possible to notice the distance between the conceptions of the creators of the courses, represented by the Municipal Education, and their target. The results give evidences that the training offered do not correspond to the needs faced by these principals and teachers, their conceptions and dilemmas are not taken into consideration to elaborate a continuing education initiative.

Neste artigo o tema da formação continuada aparece associado à análise de necessidades, conforme a fundamentação teórica utilizada. O objetivo dele foi identificar os fatores que motivam e desmotivam a formação continuada dos gestores educacionais (diretores, vices, coordenadores pedagógicos e assistentes educacionais pedagógicos) de dez escolas municipais da cidade de Araraquara. Os gestores foram ouvidos mediante questionário, relato de narrativas e entrevistas; e o posicionamento da Secretaria Municipal de Educação através de uma entrevista. Conforme o relato destes gestores foi possível perceber a distância entre as concepções dos idealizadores das formações representados pela Secretaria Municipal de Educação e o público alvo delas. Os resultados demonstram que as formações oferecidas não correspondem às necessidades vivenciadas por estes gestores e professores; suas concepções e dilemas não são levados em consideração ao se elaborar uma iniciativa de formação continuada.
The continuous graduation of education managers
Keywords: Continuing education; Needs analysis; Public school managers; Formação continuada; Análise de necessidades; Gestores da escola pública